Optimalisasi Individual Effort, Organizational Effort dan Environment Effort Pemuda Karang Taruna Dalam Meningkatkan Daya Tanggap (Responsiveness) Kondisi Darurat Wabah COVID-19 - Atiek Murharyati; Dwi Sulisetyowati; Erinda Nur Pratiwi; Siti Nurjanah (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2021)
Taruna coral organization has an important role to face the Covid 19 outbreak, because it has good resilience and a reliable way of thinking,so that it can be done optimization of taruna coral organization in keeping the spread of Covid 19 is not more widespread. Based on this, the youth of taruna coral needs strengthening of the organization so that it will increase the powerof the ladder p(responsiveness) smart youth. The purpose of community service is to strengthen the organization of taruna coral so that it can become an organization that has high responsiveness to the environmental situation due to Covid through the strengthening of individual efforts, organizational efforts and environment efforts. Some things that need to be strengthened are individual effort, organizational effort and environment effort. The method is done by educating young people in the form of lectures and mentoring activities in the face of the Covid 19 pandemic outbreak. The results were realized that after the education of 100% members of taruna coral realize and know the importance of strengthening the organization through strengthening individual effort, organizational effort and environment effort. And after mentoring activities in the form of social service, 100% of taruna coral members are able to do activities as a form of responsiveness to the occurrence of the covid 19 outbreak, namely by the form of social service activities of distribution of foodstuffs and Brochures covid 19 to citizens. The conclusion is that taruna coral organizations can run programs by fostering and strengthening individual efforts, organizational efforts and environment efforts so as to have responsiveness to the environmental situation due to Covid 19.